A BIBLIOMETRIC ANALYSIS: RESEARCH OF URBAN FARMING IN INDONESIA PERIOD 1991-2023 - Rochim, Nazulah Mufarichah; Heriqbaldi, Unggul (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
This research is related to urban farming as a major variable in this publication. The aim of this research is to investigate the profile of original scientific articles along with reviews on the topic of urban farming in Indonesia in the period 1991-2023 using bibliometric analysis. Journals related to urban farming in Indonesia published between 1991-2023 are taken from Scopus. The records analyzed and taken from the research material as characteristic of the subsequent quotation containing the distribution of the author's name, year of publication, principal author institution, publisher processed using Microsoft Excel 2016 and VOSviewer v.1.61 are used to create bibliometric diagrams. A total of 81 journals published in Scopus were written by 160 identified authors. The number of published articles continued to increase from 1991 to 2023, with the majority of articles written in English. The most cited article is Aquaculture Research with a 10-year quotation. Visualization analysis based on the accuracy of connected words in titles and abstracts has revealed several groups of research. This research contributes to providing a systematic overview of the productivity and visibility of research projects focused on urban farming in Indonesia, which is expected to be used to organize and prioritize future research.